Nova metodologija za procjenu rizika statodinamičkih napora : Smart metoda - Bubaš, Marija (Array, 2018)
This paper describes development of a new tool, a Scoring Method for Assessment of Repetitive Tasks. This new numerical assessment makes possible to measure and evaluate both, tasks with high repetition and hard manual work. It is aimed at surveillance and detection of occupational health risks causing occupational musculoskeletal diseases.A comprehensive and critical review of the literature was conducted prior to designing the tool, together with follow-up evaluations of own studies. The new tool includes an objective description of tasks, repetition, force and body posture. Demands of work are presented with scores, each in individual scale which corresponds to the conditions encountered in practice. The classification of these scales and final numerical quantification gives an indication of overload and of load bottlenecks. Total numerical score is obtained by multiplying the scale value for the daily duration by the sum of other scale values. End result is a total score, with numerical value, describing the risk of physical overload. Numerical value is explained in explanatory table which contains four ranges of numerical values, also coloured in: green, yellow, orange and red accordingly with the level of risk. Until now, the draft method was tested and found easier to handle in the field, with fair correlation of results when assessing strains compared to results of other tested tools, providing easy numerical quantification of manual tasks with high repetition, occasional force exertion and awkward body postures together with their interaction. The draft is now in the further process of field testing and scientific evaluation.